2018
DOI: 10.1371/journal.pone.0200657
|View full text |Cite
|
Sign up to set email alerts
|

Modeling APC mutagenesis and familial adenomatous polyposis using human iPS cells

Abstract: Mutations in the gene Adenomatous Polyposis Coli or APC appear in most sporadic cases of colorectal cancer and it is the most frequent mutation causing hereditary Familial Adenomatous Polyposis. The detailed molecular mechanism by which APC mutations predispose to the development of colorectal cancer is not completely understood. This is in part due to the lack of accessibility to appropriate models that recapitulate the early events associated with APC mediated intestinal transformation. We have established a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 45 publications
2
26
1
1
Order By: Relevance
“…Therefore, we conclude that monoallelic APC expression is sufficient for the maintenance of self‐renewal of hESCs. This is in contrast to the findings of Sommer et al that showed significant spontaneous differentiation of iPSC already with monoallelic APC expression.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Therefore, we conclude that monoallelic APC expression is sufficient for the maintenance of self‐renewal of hESCs. This is in contrast to the findings of Sommer et al that showed significant spontaneous differentiation of iPSC already with monoallelic APC expression.…”
Section: Discussioncontrasting
confidence: 99%
“…However, in all isolated clones harboring CRISPR/ Cas9-induced heterozygous frameshift mutations, full length APC protein expression was maintained, indicating that the mutation occurred in the germline-mutant allele rather than the WT allele. Congruently, none of the isolated clones had a homozygous loss of function mutation in both APC alleles, in line with recent results by Sommer et al [50].…”
Section: Discussionsupporting
confidence: 89%
“…Patient HIOs are suitable for disease modeling. While the translational potential of organoids to the ultimate goal of cell or tissue replacement therapy is still years away, they have already demonstrated significant utility in disease modeling, particularly in the context of monogenic disorders such as Familial Adenomatous Polyposis (FAP) 46 and cystic fibrosis (CF) 12,47,48 . In CF, cell-based models have proved invaluable in developing CFTR modulators.…”
Section: Mf Hios Contain a Variety Of Intestinal Epithelial Cell Typesmentioning
confidence: 99%
“…Additionally, they demonstrated that WNT signaling was suboptimal in HIOs derived from DC patient iPSCs and that this could be compensated by the addition of a WNT agonist which resulted in increased telomerase activity, telomere length and telomere capping. Additionally, two different groups generated iPSCs from patients with Familial adenomatous polyposis (FAP) (16,42). Both groups were able to demonstrate that organoids grown from FAP patient-derived iPSCs exhibited increased WNT signaling compared to controls.…”
Section: Genetic Tools In Hio Researchmentioning
confidence: 99%